A Comparative Clinical Study to Evaluate the Efficacy of Nayopayam Syrup and Vyaghryadi Syrup in the Management of Tamaka Shwasa (International Journal of Ayurveda and Pharma Research, 2022)
Tamaka shwasa is a Pitta Sthana Samudbava Pranavaha srotovikara in which the aggravated Kapha and Vata doshas plays a major role in causing Sthanasamshraya in the Pranavaha srotas, where Udrita kapha gets accumulated and causes obstruction to the normal movement of Prana Vata, which ends up in Pratiloma Gati of Vata producing the Lakshanas of Shwasa. This pathology is similar with that explained in modern i.e., bronchial asthma, where the inflammation of the airway is produced by broncho-constriction. The peak incidence of bronchial asthma is seen in 5 to 10 years of age group. Its prevalence range is 4 to 32% for 6 to 7 years old children. In childhood, there is a 2:1 male/female preponderance but the sex ratio gets equalizes by age 30. The prevalence of bronchial asthma is increasing by age worldwide. Nayopayam Kashayam and Vyaghryadi Kashayam having Vatakaphahara and Shawasahara property, mentioned in Arogya Raksha Kalpa Drumam and Ashtanga Hrdayam respectively are the formulations taken for the study